Environmental Changes as a Factor in the Dynamics of Aquatic Vegetation Distribution in Belarusian Soft-Water Lakes - Nina Sukhovilo; Daria Vlasova; Aliaksei Novik; Boris Vlasov (Limnological Review)
This article describes the reasons for and trends in the overgrowth of soft-water lakes in Belarus. Due to their unique water properties (low mineralization, pH, and nitrogen and phosphorus concentrations) and high water transparency, soft-water lakes are home to protected plant species like Lobelia dortmanna L., Isöetes lacustris L., and Littorella uniflora L. The purpose of this study was to analyze changes in aquatic vegetation distribution in seven soft-water Belarusian lakes and identify the causes of these changes. The initial data for this research were the results of field observations, the archive materials of the research laboratory of lake research conducted by the Belarusian State University for the period from 1971 to 2016, including morphometric and hydrochemical parameters, the characteristics of catchments and water exchange, and the results of studying the species composition and distribution of aquatic vegetation. The authors’ field studies were carried out in 2022–2024. We used expeditionary, hydrochemical, cartographic, and comparative research methods. The most significant changes in overgrowth were observed in Lakes Svityaz and Beloe (Luninets District). These lakes have high recreational loads. Significant negative trends were also noted in Lakes Bolshoe Ostrovito and Bredno. Over 35 years, the depth of distribution of submerged macrophytes in Lake Svityaz has decreased from 7 to 2 m, and the abundance and projective cover of semi-submerged macrophytes have increased. In Lake Beloe, I. lacustris, which forms a tier of submerged plants, has almost completely disappeared, and a previously absent strip of air-aquatic plants has formed. The total area of overgrowth in the lake has decreased from 35% of the water area to 3.2%. In Lake Bolshoe Ostrovito, Fontinalis sp., previously common at depths of up to 5 m, has practically disappeared. In Lake Bredno, the water moss Drepanocladus has spread to a depth of 4 m. In Lake Glubokoe, a new area of I. lacustris growth was discovered around an island at depths of up to 4 m. In Lake Cherbomyslo, the decrease in the species’ depth and area of distribution is associated with a weakening of the inflow of bog waters due to their backwater. The main causes of these changes are largely due to anthropogenic factors (water pollution by biogenic compounds) and, to a lesser extent, hydrological changes (decrease in the moisture content of lake catchments).